The Relationship Between Level Of Knowledge And Personal Hygiene During Mestruation Among Students Of Class VII MTSN 6 Padang City - Ulfa Hulkarimah; Rosfita Rasyid; Muhammad Syauqi (Lembaga Pengembangan Kinerja Dosen, 2024)
Adolescent girls who have experienced menstruation need to know how to maintain their reproductive health. If someone has poor knowledge about personal hygiene during menstruation, it can increase the risk of getting Reproductive Tract Infections (ISR). This study aimed to assess the correlation between the level of knowledge with personal hygiene practice during menstruation among female student grade VII of MTsN 6 Padang. This study is an observational analytic study with a cross-sectional design was at MTsN 6 Padang in February - March 2022. The sample in this study were girl students grade VII of MTsN 6 Padang who had experienced menstruation as many as 68 respondents. Data were obtained from questionnaires distributed to respondents. The results of this study regarding the level of knowledge showed that respondents had a good level of knowledge (48,5%) and good personal hygiene practice during menstruation (54,4%). The results of the bivariate analysis of the correlation between the level of knowledge with personal hygiene practice during menstruation obtained p value = 0.000 (p <0.05). The conclusion of this study is that there is a correlation between the level of knowledge with personal hygiene practice during menstruation among female student grade VII MTsN 6 Padang.